INNOVATIVE WAYS OF TEACHING A FOREIGN LANGUAGE IN NON-LINGUISTIC UNIVERSITIES USING MODERN GADGETS (Journal of Universal Science Research, 2024)
In today's globalized world, proficiency in foreign languages is a valuable skill across various fields, including science, engineering, business, and more. However, non-linguistic universities often face challenges in effectively teaching foreign languages due to limited resources and specialized faculty. The advent of modern gadgets and technology offers innovative solutions to these challenges. This article explores various ways in which modern gadgets can be utilized to enhance the teaching and learning of foreign languages in non-linguistic universities. We review existing literature, describe our methodology for data collection, present innovative methods, and discuss the implications of these methods for language teaching.